Transforming realities: An analysis of the reports of the CDC women’s commissions - Sena, Sandy Patrycia Teixeira; Teixeira, Marlise Alves Silva; Sousa, Elizabeth Alline de; Canindé, Janaína dos Santos; Lima, Eva Schran de; Santos, Ticiane Lima dos (Seven Editora, 2024)
The present work proposes to carry out a detailed analysis of the reports of the commissions of the CDC Women, with the objective of understanding and revealing the feminine force that has driven transformations in the professional field and in gender equality. Based on references from relevant scientific articles, a deep dive will be carried out in the reports of the commissions, aiming to identify the achievements achieved by women and the main themes addressed. Therefore, this work assumes as its general objective to analyze the reports of the commissions of the CDC Women, highlighting issues related to the promotion of gender equality and women’s empowerment in the accounting field. The methodology adopted was content analysis. From the results obtained, we observed that most of the reports presented data recognizing the importance of women’s commissions in their respective CDCs, highlighting the performance of these commissions in the promotion of events, lectures, meetings and campaigns related to gender issues and women’s empowerment in the accounting field. In addition, we noticed the appreciation of the exchange of experiences and mutual support among the women accountants, strengthening sisterhood and unity among them. DOI:https://doi.org/10.56238/sevened2023.006-135